2019
DOI: 10.1177/0040517519873875
|View full text |Cite
|
Sign up to set email alerts
|

Retarding the decay of temperature in the air flow field during the melt blowing process using a thermal insulation tube

Abstract: During melt blowing, most of the polymer jet attenuation occurs in the area within 2 cm from the die, due to the rapid decrease of polymer jet temperature. Therefore, keeping the polymer jet temperature above melting point for a longer time is beneficial for its attenuation. Here, a thermal insulation tube with heating ability was introduced into the air flow field during the melt blowing process. The computational fluid dynamics technique was employed to investigate the effects of the thermal insulation tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, as the melt-blowing air is turbulent, we believe measurements which obtain only the mean airflow characters are still inadequate and not representative. CFD is the other widely used way to investigate the melt-blowing airflow field [ 8 , 19 , 20 , 21 ], owing to its advantage of saving costs. Tan et al performed the simulation work of the airflow field formed by the slot-die nozzle with a laval add-on device [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the melt-blowing air is turbulent, we believe measurements which obtain only the mean airflow characters are still inadequate and not representative. CFD is the other widely used way to investigate the melt-blowing airflow field [ 8 , 19 , 20 , 21 ], owing to its advantage of saving costs. Tan et al performed the simulation work of the airflow field formed by the slot-die nozzle with a laval add-on device [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The fiber diameter and morphology of melt-blown nonwovens are mainly determined by the airflow field, while the airflow field is determined by the die configuration. 16,17 Many works have been devoted to reducing the fiber diameter by improving the die configuration. The designs of the die configuration are mainly divided into two categories: one is the design of the die itself, and the other involves employing add-on components to the existing die.…”
mentioning
confidence: 99%
“…Air jets produced by the A design have a higher velocity than those produced by the B design, as shown in Figure 12, which minimizes nozzle inefficiencies such as excessive air recirculation and entrainment, which have been studied by several authors. 11,51,52 In line with this observation, Shambaugh et al 25 developed a numerical 1D model for studying MB fiber attenuation, showing that the introduction of a "velocity plateau" in the air velocity field translated into significant savings in terms of air consumption.…”
Section: ■ Resultsmentioning
confidence: 92%
“…Given that K ranged from 26.57 to 46.13 (mean 35.57) in the A design and from 22.44 to 29.82 (mean 26.13) in the B design, it is concluded that the A design allows either similar or higher air drag to be reached than the B design, when each design operates under its typical operating conditions. Air jets produced by the A design have a higher velocity than those produced by the B design, as shown in Figure , which minimizes nozzle inefficiencies such as excessive air recirculation and entrainment, which have been studied by several authors. ,, In line with this observation, Shambaugh et al developed a numerical 1D model for studying MB fiber attenuation, showing that the introduction of a “velocity plateau” in the air velocity field translated into significant savings in terms of air consumption.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation